Research on the dynamic characteristics of the electromagnetic repulsion mechanism of a self-driving fault current limiter - Song, Rui; Ding, Yujie; Wang, Xuebin; Fu, Guobin; Si, Junjie; Wang, Da; Chen, Xiaoyue; Ai, Shaogui (Frontiers in Energy Research, 2024)
A fault self-driven current limiter is proposed in the paper, which uses a special fault current direct-driven electromagnetic repulsion mechanism to realize the first half-wave of the fault current over the zero point into the current-limiting reactance. The paper analyzes the working principle of the self-driven electromagnetic repulsion mechanism, establishes the equivalent model of the mechanism, and simulates the dynamic characteristics of the electromagnetic repulsion mechanism through the calculation of the double-layer iterative algorithm in time and space. The LC oscillation loop test platform is built, and the stroke–time curve of the prototype is measured. In the test, the prototype is driven by a 3 kA current, and the first half-wave stroke (FHWS) is 3.55 mm past the zero point, which is consistent with the simulation and test results. The effects of structural parameters such as the radius, thickness, and number of turns of the self-driven electromagnetic repulsion mechanism on the dynamic characteristics of the electromagnetic repulsion mechanism are investigated, and it is found that the first half-wave stroke can be significantly improved by increasing the number of turns and outer diameter of the coil. The optimum height of the dynamic repulsion coil is approximately 3 mm.